The Effect of Person Organizational Fit Mediated by Knowledge Sharing and Organizational Citizen Behavior on Innovative Work Behavior in Marketing Employees - Hindun Silalahi*; Muhammad Irfan Nasution (Riwayat: Educational Journal of History and Humanities, 2023)
The term "innovative behavior" in the workplace refers to an individual's or group's desire to develop, generate, and implement novel concepts to enhance performance. Inventive way of behaving has additionally been inspected according to the viewpoint of individual association fit. Different investigations have broke down what individual hierarchical fit means for inventive work conduct, additionally with inconsistent outcomes. The results of testing the SEM-PLS method on a sample of 133 Slovin formula respondents indicate that to increase innovative work behavior in employees,oyees, organizational fit, knowledge sharing, and organizational citizenship behavior are needed. In organizations, person-organization fit refers to the suitability or harmony between individual characteristics and the values that exist in the organization. Apart from individual organizational fit and knowledge sharing, organizational citizenship behavior also has an influence on innovative work behavior. Organizational citizenship behavior is the behavior possessed by employees to contribute to the company beyond their obligations or demands. To increase innovative work behavior in marketing employees, person-organizational fit and organizational citizen behavior are needed, which are mediated by knowledge sharing. If employees have personal organizational fit, they will contribute more to producing innovation and more effective performance. Therefore, companies need to maintain personal organizational fit, one of which is by encouraging a culture of sharing knowledge between employees.